Educational policy-making and hegemony: monolithic voices from civil society. Issue 8 (17th November 2019) - Karlidag-Dennis, Ecem; McGrath, Simon; Stevenson, Howard
Abstract: This article discusses the changes in basic education in Turkey, with a particular focus on religious education and its ramifications for the education system. The latest education reform, 4 + 4 + 4 (or 4+), the largest education reform in recent Turkish history, has brought radical changes to the school system regarding religious education. For this research, journalists and teacher unionists were interviewed to investigate civil society's perspective on the reform. Several themes were extracted from the data analysis but this article focuses on one dominant theme, namely the rise of religiosity. We argue that the state and its private associations (i.e. media, unions and political parties) are actively encouraging a process of Islamisation and a gradual but stronger emphasis on Islam in the public sphere in order to consolidate its hegemonic dominance.